Stillbirth Associated With Infection in a Diverse U.S. Cohort. Issue 6 (December 2019) - Page, Jessica M.; Bardsley, Tyler; Thorsten, Vanessa; Allshouse, Amanda A.; Varner, Michael W.; Debbink, Michelle P.; Dudley, Donald J.; Saade, George R.; Goldenberg, Robert L.; Stoll, Barbara; Hogue, Carol J.; Bukowski, Radek; et al.
Abstract : OBJECTIVE: To better characterize infection-related stillbirth in terms of pathogenesis and microbiology. METHODS: We conducted a secondary analysis of 512 stillbirths in a prospective, multisite, geographically, racially and ethnically diverse, population-based study of stillbirth in the United States. Cases underwent evaluation that included maternal interview, chart abstraction, biospecimen collection, fetal autopsy, and placental pathology. Recommended evaluations included syphilis and parvovirus serology. Each case was assigned probable and possible causes of death using the INCODE Stillbirth Classification System. Cases where infection was assigned as a probable or possible cause of death were reviewed. For these cases, clinical scenario, autopsy, maternal serology, culture results, and placental pathology were evaluated. RESULTS: For 66 (12.9%) cases of stillbirth, infection was identified as a probable or possible cause of death. Of these, 36% (95% CI 35–38%) were categorized as a probable and 64% (95% CI 62–65%) as a possible cause of death. Infection-related stillbirth occurred earlier than non–infection-related stillbirth (median gestational age 22 vs 28 weeks, P =.001). Fetal bacterial culture results were available in 47 cases (71%), of which 35 (53%) grew identifiable organisms. The predominant species were Escherichia coli (19, 29%), group B streptococcus (GBS) (8, 12%), and enterococcus species (8, 12%). Placental pathology revealed chorioamnionitis in 50 (76%), funisitis in 27 (41%), villitis in 11 (17%), deciduitis in 35 (53%), necrosis in 27 (41%), and viral staining in seven (11%) cases. Placental pathology found inflammation or evidence of infection in 65 (99%) cases and fetal autopsy in 26 (39%) cases. In infection-related stillbirth cases, the likely causative nonbacterial organisms identified were parvovirus in two (3%) cases, syphilis in one (2%) case, cytomegalovirus (CMV) in five (8%) cases, and herpes in one (2%) case. CONCLUSION: Of infection-related stillbirth cases in a large U.S. cohort, E coli, GBS, and enterococcus species were the most common bacterial pathogens and CMV the most common viral pathogen. Abstract : Most cases of infection-related stillbirth are due to bacterial pathogens, of which Escherichia coli, group B streptococcus, and enterococcus species are the most common.